Efektivitas Penggunaan Obat Dislipidemia terhadap Kadar LDL pada Pasien Cardiovaskular Penyebab Stroke - Rahmawati Raising; Oktaviarika Dewi Hermawatiningsih; Wiwi Rumaolat (Yayasan Literasi Sains Indonesia, 2024)
Dyslipidemia is one of the main risk factors for cardiovascular disease, and cholesterol management therapy has significant benefits in the primary and secondary prevention of coronary heart disease and stroke. Therefore, lipid-lowering therapy, especially using HMG-CoA reductase inhibitors (statins), aims to assess the effectiveness of using statin-class dyslipidemia medications, such as simvastatin and atorvastatin, in reducing LDL levels in cardiovascular patients at X Hospital. This research method uses an observational analytic study with a retrospective research design. This study employs the purposive sampling method. The results of this study show that the majority of patients are female (75%). Based on age grouping, it was found that the highest proportion of patients were aged 56-65 years, accounting for 45%. The use of dyslipidemia drugs that achieved the target LDL reduction ≥ 50% includes Simvastatin 10 mg (33.82%), Simvastatin 20 mg (11.94%), Atorvastatin 10 mg (10.45%), and Atorvastatin 20 mg (41.79%). The most effective drug in achieving the LDL reduction target was Atorvastatin 20 mg.